2015
DOI: 10.3389/fnhum.2015.00555
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sung speech on socio-communicative responsiveness in children with autism spectrum disorders

Abstract: There is emerging evidence to demonstrate the efficacy of music-based interventions for improving social functioning in children with Autism Spectrum Disorders (ASD). While this evidence lends some support in favor of using song over spoken directives in facilitating engagement and receptive intervention in ASD, there has been little research that has investigated the efficacy of such stimuli on socio-communicative responsiveness measures. Here, we present preliminary results from a pilot study which tested wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 62 publications
2
34
0
Order By: Relevance
“…Our data also corroborated music selectivity, particularly in the anterior portion of the secondary auditory cortex (planum polare), which was independent of whether the musical stimuli contained lyrics or not. Finally, these results provide more evidence supporting music-based therapies as a complementary way to address motor impairments [68][69][70][71] and communicative skills, as has been demonstrated in social behaviors in children with autism [72][73][74] .…”
Section: Discussionsupporting
confidence: 56%
“…Our data also corroborated music selectivity, particularly in the anterior portion of the secondary auditory cortex (planum polare), which was independent of whether the musical stimuli contained lyrics or not. Finally, these results provide more evidence supporting music-based therapies as a complementary way to address motor impairments [68][69][70][71] and communicative skills, as has been demonstrated in social behaviors in children with autism [72][73][74] .…”
Section: Discussionsupporting
confidence: 56%
“…The current analysis was performed in the context of a completed proof‐of‐concept study and an ongoing randomized clinical trial, comparing auditory‐motor mapping training (AMMT), a novel treatment that uses intonation (singing) and rhythmic hand tapping to facilitate sound‐motor mapping and/or to improve speech output in MV children with ASD, with speech repetition therapy (SRT), a control treatment that involves neither intonation nor hand tapping. AMMT is one of a small number of music‐based treatments that have recently begun to be used effectively for teaching language and social skills to children with ASD [see e.g.,Lim, ; Lim & Draper, ; Paul et al, ]. In an earlier proof‐of‐concept study involving AMMT alone, significant improvement in production of two‐syllable words and phrases was observed over 40 treatment sessions in six MV children with ASD [Wan et al, ], with levels of improvement ranging from 8% to 71% across participants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Paul et al (2015) showed that singing directives, rather than speaking them, resulted in a greater response rate to name and to social gestures in three MV children with ASD. However, Lim and Draper (2011) showed that sung instructions were as effective as spoken instructions in eliciting four types of verbal communication in 22 verbal and preverbal preschool children with ASD.…”
Section: Introductionmentioning
confidence: 99%